Prometni koridorji in poselitev v regiji - Šašek-Divjak, Mojca (Urbani izziv, 2004)
The focus of the article is conditioning settlement to public transport on theregional and urban level. Similar to occurrences in Western Europe even in Slovenia strong settlement pressures and issues tied to development of suburbanisation are emerging in wider hinterlands of larger cities. In regional centres, where strong transport flows with frequent congestion happen, public transport should be the backbone of the transport system. It isimportant for consolidation of larger gravitation areas, especially conurbations. We can nevertheless establish that parallel to increasing use ofprivate cars, the use of public transport is decreasing. Thus the present condition demands improvements of transport systems and suitable settlement density in conjunction with development of public transport. This can be achieved only by synergetic linking of public transport development and physical planning in a sustainable settlement system. In the Ljubljana functional region we specifically dealt with links between settlement and the regional public transport system, above all the proposed regional light-railway and tram system in the strict urban area. The decentralised denser settlement model is presented. Based on the study concerning settlement.
Keywords: decentralizacija; infrastructure; infrastruktura; javni promet; naselja; prometno omrežje; suburbanizacija; urbani razvoj; urbanizacija